TINJAUAN MANAJEMEN LOGISTIK OBAT DI INSTALASI FARMASI DINAS KESEHATAN PROVINSI SUMATERA UTARA - Rangkuti, Muhammad Al Fatih; Berutu, Edy Putra; Rangkuti, Agus Edy (Universitas Dharmawangsa, 2024)
This study aims to review the drug logistics management at the Pharmacy Installation of the Provincial Health Office of North Sumatra. The main focus of this research is on the planning, procurement, storage, and distribution processes of drugs conducted in the installation. This research employs a qualitative approach with data collection through interviews and direct observations in the field. The results indicate that drug logistics management at the Pharmacy Installation of the Provincial Health Office of North Sumatra has been well implemented, although there are still some challenges related to the information system and interdepartmental coordination. The study recommends enhancing the integration of information technology into the drug logistics management process to improve service efficiency and effectiveness.